PENGEMBANGAN MEDIA LAPBOOK UNTUK MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA - Natasya, Wina Patrisiya; Kurnia, Ira Restu (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This study aims to develop Lapbook learning media and test the feasibility of Lapbook learning media in order to increase student interest in learning. This research is included in Research and Development (RnD) research which uses the ADDIE development model in Sugiyono's book with 5 stages, namely: 1) analysis; 2) product design; 3) development; 4) implementation; 5) evaluation. The subjects of this study were third grade students of SDN Sukadami 04 with data collection techniques conducting interviews, for respondents in this study, namely media, language and material experts as well as media users, namely homeroom teachers and students. This study found that: (1) Lapbook learning media is declared feasible by the material with a percentage of 90% material feasibility assessment including very feasible criteria, 94% language feasibility assessment with very feasible criteria and 100% media feasibility; (2) Lapbook learning media is declared very effective by class teachers with a percentage of 95% and students 98.6%. The conclusion of this study is that Lapbook learning media is declared feasible for use in science pedagogical subjects with material on Changes in the Form of Objects. Input from this study, so that the use of media in learning activities is further enhanced as needed.